Suppressing glucose metabolism with epigallocatechin-3-gallate (EGCG) reduces breast cancer cell growth in preclinical models. Issue 11 (12th October 2018) - Wei, Ran; Mao, Limin; Xu, Ping; Zheng, Xinghai; Hackman, Robert M.; Mackenzie, Gerardo G.; Wang, Yuefei
Abstract : EGCG reduces breast cancer growth through the inhibition of key enzymes that participate in the glycolytic pathway and the suppression of glucose metabolism. Abstract : Numerous studies propose that epigallocatechin-3-gallate (EGCG), an abundant polyphenol in green tea, has anti-cancer properties. However, its mechanism of action in breast cancer remains unclear. This study investigated the capacity of EGCG to suppress breast cancer cell growth in vitro and in vivo, characterizing the underlying mechanisms, focusing on the effect of EGCG on glucose metabolism. EGCG reduced breast cancer 4T1 cell growth in a concentration- (10–320 μM) and time- (12–48 h) dependent manner. EGCG induced breast cancer apoptotic cell death at 24 h, as evidenced by annexin V/PI, caspase 3, caspase 8 and caspase 9 activation. Furthermore, EGCG affected the expression of 16 apoptosis-related genes, and promoted mitochondrial depolarization. EGCG induced autophagy concentration-dependently in 4T1 cells by modulating the levels of the autophagy-related proteins Beclin1, ATG5 and LC3B. Moreover, EGCG affected glucose, lactate and ATP levels. Mechanistically, EGCG significantly inhibited the activities and mRNA levels of the glycolytic enzymes hexokinase (HK), phosphofructokinase (PFK), and lactic dehydrogenase (LDH), and to a lesser extent the activity of pyruvate kinase (PK). In addition, EGCG decreased the expression of hypoxia-inducible factor 1α (HIF1α) and glucose transporter 1 (GLUT1), critical players in regulating glycolysis. In vivo, EGCG reduced breast tumor weight in a dose-dependent manner, reduced glucose and lactic acid levels and reduced the expression of the vascular endothelial growth factor (VEGF). In conclusion, EGCG exerts an anti-tumor effect through the inhibition of key enzymes that participate in the glycolytic pathway and the suppression of glucose metabolism.